Pemberdayaan Kelompok Guru Dalam Membuat Media Pembelajaran Pop-Up Digital - Nurzengky Ibrahim; Desy Safitri; Sujarwo Sujarwo; Iqbal Pratama (Indo Publishing, 2026)
This empowerment initiative was motivated by teachers' limited competence in developing digital learning media that facilitate formative feedback for students. Digital pop-up media serve as interactive learning tools that provide visual and contextual feedback in response to student learning activities. The objective of this activity was to empower a group of teachers at SMPN 20 Jakarta to design and develop digital pop-up media as tools for providing learning feedback. The initiative was conducted through in-person sessions comprising lectures, interactive discussions, demonstrations, simulations, and pre- and post-test questionnaires. The results demonstrate an improvement in the teachers' knowledge, understanding, and skills regarding digital pop-up media development; this is evidenced by the participants' ability to create feedback-oriented pop-up products such as automatic response confirmations, concept-reinforcement pop-ups, and reflective feedback notifications tailored to their respective subjects. This activity is expected to strengthen teachers' digital-pedagogical competence and serve as an empowerment model that can be replicated within the broader teaching community